2017
DOI: 10.1063/1.4994027
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced properties of Bis-azo chromophore host guest systems-birefringence and all optical tuneable polymer waveguide Bragg gratings

Abstract: The photoinduced properties of recently synthesised and reported bis-azo dyes doped host-guest polymer films were investigated. The photochromic properties and photoinduced birefringence were characterised. The birefringence was found to be very stable, and 96% of the birefringence was retained after illumination of the films was stopped. The high two photon absorption cross section (1251GM) together with stable photoinduced birefringence makes these materials promising candidates for 3D optical storage. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This phenomenon could be associated with the presence of the memory effect [58]. The obtained results allow a comparison to be made with the birefringence behaviour of most used azo-polymers or azo dyes embedded in a polymer matrix [59]. Recently, Schab-Balcerzak and co-workers have synthesized and investigated several azobenzene poly(amide imide)s [60] and azobenzene poly(esterimide)s [61] in terms of their photoanisotropic behaviour [62,63].…”
Section: Resultsmentioning
confidence: 96%
“…This phenomenon could be associated with the presence of the memory effect [58]. The obtained results allow a comparison to be made with the birefringence behaviour of most used azo-polymers or azo dyes embedded in a polymer matrix [59]. Recently, Schab-Balcerzak and co-workers have synthesized and investigated several azobenzene poly(amide imide)s [60] and azobenzene poly(esterimide)s [61] in terms of their photoanisotropic behaviour [62,63].…”
Section: Resultsmentioning
confidence: 96%
“…Calculation of energy of the inter‐valence band of tris‐azobenzene A‐21 radicals showed that the electronic coupling between consecutive charge‐bearing azobenzene units is more than the bis‐azobenzene radicals studied. Photo‐induced birefringence of different linear, non‐linear and core‐based bis‐azo chromophores A‐22 , [24a] A‐23 [24b] and A‐24 , [24c] doped within host‐guest polymer films, were explored and in some cases, utilized for manufacturing an all‐optical integrated device (Figure 5). Hecht, Grill and co‐workers deposited bis‐azobenzenes A‐16 and A‐25 , with electronically coupled and decoupled arrangements of azo units, on Au surface [25a] .…”
Section: Type‐1: Linear Branched and Core‐based Multiazoarene Systemsmentioning
confidence: 99%
“…In the last decades, light-responsive molecules have been of interest in many applications, such as optical data storage, optical switches, optical memory, etc., [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%